Analisis Stabilitas Sistem Tenaga Listrik Dengan Automatic Generation Control (AGC) Dua Area Menggunakan Fuzzy Logic Controller - Noviantara, Made Dwi; Suweden, I Nengah; Mataram, I Made (Majalah Ilmiah Teknologi Elektro, 2018)
The power system must be able to server the load in a sustainable manner with good service quality, such as constant voltage and frequency, quickly stabilized when load changes occur. The control generator automatically changes the frequency to the highest value when the system changes every time. This is called AGC. To keep the frequency in a stable state required frequency control system. Currently developing a lot of control system with fuzzy logic method. The simulation is performed using 5 membership functions and gives a loading of 0.1 pu, using MATLAB-Simulink software. From the analysis result, the comparison of output of frequency response in overshoot condition with conventional method yielded , settling time of 20.5 second. While the fuzzy logic controller method produces frequency response output in the overshoot state that is , settling time is 12 seconds. Whit the fuzzy logic controller method produces better performance and faster than conventional methods.